Daily field checking list by Walter Rosene, September 23, 1934 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated September 23, 1934. This checklist was used by Walter Rosene to record birds sighted enroute to Algona starting at 9:00. Plustek--flatbed